PENGARUH ORIENTASI KEWIRAUSAHAAN TERHADAP PEMBELAJARAN ORGANISASI,KEUNGGULAN DAYA SAING BERKELANJUTAN DAN KINERJA USAHA PADAUMKM KERAJINAN KULIT BERORIENTASI EKSPOR DI SIDOARJO - Reswanda Reswanda (Jurnal Ekonomi Akuntansi dan Manajemen, 2012)
The objective of this research was tested the effect of entrepreneurships orientation towards organizational learning, sustainable competitive advantage and business performance of Micro, Small and Medium Enterprises (MSME) Handycraft Leather-based Export Oriented at Tanggulangin, Sidoarjo. The study was a confirmatory carries out by testing several hypotheses in order to figure out the causal relationship of all the above variables. All Micro, Small and Medium Enterprises (MSME) Handycraft Leather-based Export Oriented at Tanggulangin, Sidoarjo, 110 MSME all together were taken as the population of this research. The study employed complete enumeration or census method; hence, sample and sampling technique were not required. The technical analysis applied to test the research hypothesis was Structural Equation Modeling (SEM) with the support of AMOS 16.0 program. The result of research showed that there were direct, significant and positive relationships between entrepreneurship orientation and organizational learning; there were direct, significant and positive relationships between entrepreneurship orientation and sustainable competitive advantage; there were direct, significant and positive relationships between organizational learning and performance and there were direct, significant and positive relationships between sustainable competitive advantage and business performance. There were no relationships between entrepreneurship orientation and business performance and there were no relationships between organizational learning and sustainable competitive advantage at handycraft leather-based export oriented at Tanggulangin, Sidoarjo. Benefit of this research can be used as scientific information regarding the variables of entrepreneurship orientation, organizational learning, sustainable competitive advantage and business performance. It can also be used as a basis to motivate improvement small scale industry. Keywords: Entrepreneurship orientation, organizational learning, sustainable competitive advantage, business performance, micro, small and medium enterprises